2021
DOI: 10.1111/tbj.14191
|View full text |Cite
|
Sign up to set email alerts
|

Changes in utilization of axillary dissection in women with invasive breast cancer and sentinel node metastasis after the ACOSOG Z0011 trial

Abstract: The American College of Surgeons Oncology Group Z0011 (ACOSOG Z0011) trial demonstrated no survival advantage for women with clinical T1–T2 invasive breast cancer with 1–2 positive sentinel lymph nodes (SLN) who received whole‐breast radiation, and no further axillary surgery when compared to women who did undergo axillary lymph node dissection (ALND). We used the National Cancer Database (NCDB) to study changes in utilization of ALND after the publication of this trial. NCDB was queried for female patients fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Since the release of ACOSOG Z0011 and the Choosing Wisely Guidelines, rates of ALND have decreased from 100% to 17% leading to a 20% reduction in mean overall cost per patient 25–27 . However, the implementation and implications of this uptake on populations that have historically faced barriers in accessing high quality and high value oncologic care, such as marginalized and minoritized individuals, low individual and/or neighborhood SES, is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the release of ACOSOG Z0011 and the Choosing Wisely Guidelines, rates of ALND have decreased from 100% to 17% leading to a 20% reduction in mean overall cost per patient 25–27 . However, the implementation and implications of this uptake on populations that have historically faced barriers in accessing high quality and high value oncologic care, such as marginalized and minoritized individuals, low individual and/or neighborhood SES, is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there was a trend of increasing SES and higher utilization of two low value Since the release of ACOSOG Z0011 and the Choosing Wisely Guidelines, rates of ALND have decreased from 100% to 17% leading to a 20% reduction in mean overall cost per patient. [25][26][27] However, the implementation and implications of this uptake on populations that have historically faced barriers in accessing high quality and high value oncologic care, such as marginalized and minoritized individuals, low individual and/or neighborhood SES, is unclear. Emerging studies suggest minority-serving cancer centers with high-volume breast cancer cases tend to have similar uptake of clinical trial guidelines compared to academic facilities.…”
Section: Low Value Surgical Carementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies around the world have identified increasing acceptance of the Z0011 results and a change in clinical practice in relation to the standard treatment of axillary lymph nodes in patients with breast cancer [35][36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
“…If patients’ evidence micro-metastases or only 1 or 2 metastatic SLNs, ALND can be omitted without compromising the oncological outcomes. Since the publication of these studies, the ALND rate has markedly decreased worldwide [ 4 5 ]. This raises the question of whether intraoperative SLN frozen section biopsy is required.…”
Section: Introductionmentioning
confidence: 99%